Kentsel Toplumsal Hareketlerin Kentlerin Dönüşümüne Etkilerinin Değerlendirilmesi - Özdeniz, Deniz (Fen Bilimleri Enstitüsü, 2016)
Kentler ve kentsel mekanlar, tarihsel süreçte üretime bağlı ilişkiler ve ekonomik sistemlerin dönüşümünün doğrudan etki ettiği dolayısıyla da bütün sosyal ve toplumsal ilişkilerin biçimlendiği en görünür mekansal düzlemlerdir. Tarımsal üretimle ortaya çıkan kentlerden 20. yüzyılda endüstriyel üretim ve küreselleşen ekonomilerin şekillendirdiği bugünün kentlerine, fiziki mekan yeniden yapılandırılırken sosyal ve mekansal eşitsizlikler ve yeni tipte sosyal dışlanmaları beraberinde getiren toplumsal ilişkilerin üretimini de ortaya çıkarmaktadır. Batı'da 70'lerde fordist şehir planlamanın yarattığı krizlerin etkisiyle atıl kalan şehir merkezlerinin rehabilitasyonu gerekliliğiyle ortaya konan merkeziyetçi kentsel yenileme politikaları ve uygulamaları, günümüz kentsel dönüşüm pratiklerinde politik-kültürel dinamiklerin değişimiyle kurumsal temeli sivil insiyatife dayalı 'karşı-kültürel kentsel hareketler' olarak tanımlanan kentsel muhalefet dinamiklerini görünür hale getirmiştir. Modern kentlerde, kent içinde ve çevresinde yer alan çoklukla kentsel dönüşüm politikalarının bir sonucu olarak işlevlerini kaybetmiş fakat kent için kullanım ve dönüşüm değeri taşıyan 'yitik alanlar', söz konusu kentsel toplumsal muhalefetin ifade edildiği sosyo politik kentsel mekanlar olarak öne çıkmaktadır. Bu tip kentsel alanların, kentte yaşayan bireyler için faydalı ve kent mekanını dolayısıyla da kentsel yaşamı canlandırıcı bir rol üstlenmesi bakımından taşıdıkları potansiyellerin kentlerin dönüşümü ekseninde değerlendirilmesi gerekmektedir. İşgal evleri, kullanılmayan ve metruk haldeki yapılara yerleşerek, barınma ve sosyal amaçlı kullanma geleneği olarak bilinen ve Batı'da 'squatting' olarak kavramsallaşan, 70'li yıllardan beri Avrupa'nın birçok ülkesinde yaygın olarak gerçekleştirilen bir kent hareketi olarak tanımlanmaktadır. Bununla birlikte günümüz modern toplumlarında kentsel muhalefet biçimi olarak görülen işgal evi hareketleri, kentsel yaşam ve yapılı çevredeki etkileri farklı kavramlara işaret eden ve kentte yaşayan herkesin gündelik pratiklerini de doğrudan etkileyen önemli bir kentsel harekettir. İşgal evleri, farklı coğrafyalarda kendi politik ve kültürel dinamikleriyle ortaya çıkmakla beraber hemen hemen bütün Batılı ülkelerde temelde bazı ortak değerleri temel alarak şekillenmektedir. Bunlar arasında barınmaya, sosyal ve kültürel ihtiyaçları gidermeye yönelik bir mekansal örgütlenme arayışı hemen hepsinde ortak özellik olarak görünmektedir. Dolayısıyla mevcut düzenlemelerin karşısında alternatif düzen arayışında oluşu itibariyle sözü edilen kentsel işgaller bilinçli ya da bilinçsizce değiştirdiği sosyal düzen ve mülkiyet ilişkileri bağlamında politik eylemlerdir. Modernizm öncesi dönemin işgalleriyle bugünün 'kent mekanını kazanmak' adına ortaya konan işgalleri, değişen politik ve sosyo kültürel koşullar anlamında farklılaşmaktadır. Kentsel mekanın belirli ihtiyaçlara cevaben işgal edilmesi olarak da tanımlanan işgal evi eylemleri, yapılı çevreyle olan ilişkisi anlamında kentsel mekanın dönüşümünde de doğrudan bir etkiye sahiptir. Bu bağlamda işgal evleri, küreselleşen kentlerin yaşadığı kentsel çelişkilerin doğurduğu mekansal problemlere karşı yeni toplumsal ve mekansal örgütlenmeler vadeder. Bir kentsel muhalefet biçimi olan ve kentsel aktör olarak orta sınıf kentlilerin kentsel çelişkilerin giderilmesine yönelik ortaya koydukları bu örgütlenmeler diğer taraftan başka kentsel çelişki dinamiğini de barındırması adına çok katmanlı bir bakış açısıyla değerlendirilmeyi gerektirmektedir. İşgal evleri her ne kadar ilk olarak kentsel ve mekansal çelişkileri ortadan kaldırmaya yönelik ortaya çıkmış hareketler olarak düşünülse de yerel dinamikler ve diğer kentsel aktörlerle olan ilişkisi ölçüsünde münferit ve doğrudan soylulaştırmaya yönelik bir başka dönüşümün katalizörü olarak da görülebilmektedir. Avrupa'da işgal evleri ile başlayan dönüşümlerin bir kısmı, bir süre sonra bu alanların sosyal ve kültürel cazibe alanlarına dönüştürülmesiyle yatırımcılar tarafından ilgi odağı haline gelmiş, arazi rantları ve spekülasyonlarıyla da desteklenerek özellikle münferit yatırımcılar için rant aracı haline getirilmiştir. 'Yeni tip soylulaştırma' olarak da tanımlanabilecek bu dönüşüm, genellikle keşfedilen bölgeye yeni açılan kafeler, atölyeler, sergi alanları gibi yeni sosyal-rekreasyonel fonksiyonların bireysel insiyatiflerle hayata geçirilmesi şeklinde gerçekleşmektedir. Kentsel çelişkilerin karşısında ona bir çözüm olarak ortaya konan kentsel hareketler diğer taraftan mevcut yapıların bireysel insiyatiflerle dönüşümü sonucu oluşan yeni tür bir soylulaştırma hareketine hizmet etme sorunsalını da potansiyel olarak taşımaktadır. Neil Smith'in 'modern sınıfın kent merkezlerini istilası' olarak tanımladığı soylulaştırma bu noktada ister kentlinin haklarını aramak üzere mevcut büyük çaplı projelerin karşısında isterse tekil olarak karşısında durduğu dönüşüme rant odaklı bir başka dönüşümü önermesi anlamında eleştirel bir düzlemde durmaktadır. Tez kapsamında hem kentsel mekanın dönüşümünde dikkate değer bir potansiyel taşıyan hem de soylulaştırmaya neden olan kentsel dönüşümü tetikleyerek ortaya çıkardığı kentsel çelişkiler bağlamında işgal evlerinin çok katmanlı yapısı farklı yönleriyle ele alınmıştır. Bu bağlamda İstanbul'daki ilk işgal evi olan Kadıköy Yeldeğirmeni Mahallesi'ndeki Don Kişot Sosyal Merkezi ve bu bölgede sonrasında kentsel anlamda yaşanan değişimler incelenerek söz konusu değişimlerin kentsel mekana olan etkileri ve kentsel dönüşümle olan ilişkisi değerlendirilmiştir.

Cities and urban spaces are the most visible spatial planes in which all kind of social relations have been shaped, directly affiliate to transformation of economic and production systems during the history. From agricultural productive cities to industrial cities in 20th century and today's global cities social and spatial inequalities have emerged which also bring with the new type of social exclusions. The squatting, occupation or take over buildings and houses -which are abandoned or disfunctioned for long periods- and re-using hem for different purposes, has a long lasting trajectory all over Europe as well as all over the world. Beginning from 70's it is mainly in Europe where squatting has been defined as widespread 'urban social movement'. Hovewer in modern societies different types of squattings accepted as an urban political practice which has been pointed out different expansions in terms of urban life and the built environment as well as daily practices. Because of being beneficial for the people live in the cities the potentials of those urban spaces must be evaluated in the context of transformation of the cities in terms of taking role in revitalizing urban space accordingly urban life. Squats are shaped by specific fundamental common values almost in every Western countries in different regions, along side their own political and cultural dynamics. Among them; the seeking of spatial organization for eliminating to sheltering, supplying social and cultural needs appear as common characteristic in almost all. Consequently; as being against to the current organizations for alternative system, aforementioned urban occupations are political actions in the context of transmuting social order and property relations consciously or unconsciously. Occupations of pre-modernism period and today's occupations for setting out on behalf of "to get the urban space" have acquired different characteristic in terms of changing political and socio-cultural conditions. Squatter's actions which is also defined as occupying the urban space in response to specific needs, has also direct effect in transformation of urban space in terms of the relationship with the structured environment. In this context, squats are promised to new social and spatial organizations against to the spatial problems raised by the urban contradictions faced by globalized cities. However, these organizations which have been manifested as urban oppositions and revealed for the elimination of the urban contradictions of the city by middle class citizens as urban actors need to be evaluated by multilayered perspective for including another urban contradiction dynamic. Although, squats firstly are considered as the movements which came out for the abolishing urban and spatial contradictions, can also seen directly and singularly as a catalyst for the another conversion of a gentrification based on the relationship with the local dynamics and other urban actors. Some parts of the conversions which are started with squatting in Europe, after a while have become the focus of attention with transformation of those social and cultural attraction areas by investors and also have been turned into rant tool with supporting by rents and speculations of the areas especially for the individual investors. This conversion that can also be described as "New types of gentrification", is realized in the form of implementation by individual initiatives with the new social-recreational functions like cafeterias, studios, exhibition areas which generally have just opened on the discovered area. Urban movements manifest as a solution against the urban contradictions, on the other hand contains potentially the problematical of the subserve to new kind gentrification movement which come out after transformation of the current buildings with individual initiatives. Gentrification which is described like 'the occupation of the city centers by modern class' by Neil Smith, in this point it remains at a critical platform whether to be againts existing large-scale projects for the rights of the citizens or suggest another conversion of rant-based against the conversion which is singularly opposite. Within the context of the thesis, multilayered structure of the squats are discussed with different aspects both revealing urban contradictions that set off by urban transformation which also create the gentrification and having a remarkable potential on transformation of the urban space. In this regard, as being first occupied social center located in Istanbul, Don Kişot Social Center at Kadıköy Yeldeğirmeni District and the changes have been occurred afterwards in the urban context at the district are examined for evaluating the effects on the urban space and the relationship with the urban transformation. The objective and scope of work in the first part of the study are examined regarding to the basic concepts related to the transformation of the city and in the second part the size of the urban transformation methods have been examined accordingly. In this context, the cities have been examined in more detail regarding the concept of urban transformation, and affects of large capital investments of different sizes and methods on the transformation have been evaluated in terms of individual movements. In the third section having an impact on the transformation of the city New Social Movements of European geography have been researched by the effects of the transformation and urban spaces and critical analysis of both societal and social at some actors of this movement has been made accordingly. Some important urban social movements emerged in Europe in this context and social impacts of those aformentioned are evaluated by the effects of the built environment and on the social structure. In the fourth part, the squats have been analyzed by the spatial potentials and relations with the urban dynamics as refunctioning and regeneration of lost spaces. However squats practices are examined by the legislation rules particularly to the European property laws. For the fifith part of the chances of study urban renewal practices were evaluated by emerging squats in Europe and articulation of the existing urban practices. In the sixth chapter, the transformation of the city was analyzed according to the influence of the urban movements in Turkey's historical urban change. In this context, the concept of 'right to the city' in recent years have been evaluated which is also debated by the concept of urban opposition movements and the changes in  urban space. Additionaly, recently emerged urban social centers in Istanbul and Ankara which are also working as neighborhood associations are examined by being spatial reflection of urban social movements. In the last chapter the first occupied social center -Yeldeğirmeni Social Center- of Turkey which is located at Kadıköy which have been revealed by the influence of these movements in Turkey as the predecessor of other movements is evaluated by the affects of urban environment and social and urban regeneration and the similarities have been compared with the squats in Europe in terms of spatial concepts in the context of gentrification.
The Evaluation Of The Effects Of Urban Social Movements On Urban Transformations
(Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
(M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2016
Keywords: işgal; kentsel yenileme; kentsel dönüşüm; kentsel toplumsal hareketler; kentsel koruma; soylulaştırma; yeniden işlevlendirme; yitik alanlar; occupation; urban regeneration; urban transformation; urban social movements; urban conservation; gentrification; refunctioning; lost spaces